Response of maize inbred lines to two European corn borer (Ostrinia nubilalis) strains in Canada - Hudon, M.; Pitblado, R.E.; Hamilton, R.I.; Bourgeois, G.; Kuzir, S.; Girgis, R. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
In 1986 and 1987, six maize inbred lines (CM47, A619, F2, CM107, CM7, and A654) were evaluated at four locations across Ontario and Quebec for their resistance to artificially infested univoltine and lst generation bivoltine strains of the European corn borer, Ostrinia nubilalis. Three criteria were used: leaf feeding, total plant damage at harvest and length of tunnels/plant height ratio. Substantial interactions in borer damage measurements were observed between locations and years, but inbred reaction was relatively consistent. For all criteria, the univoltine strain often caused significantly more damage than the bivoltine borer. In general, A619 had the greatest resistance-tolerance with good standability until harvest. Wherever possible, evaluation of genetic resistance in maize germplasm should be conducted using the univoltine borer strain.